2012
DOI: 10.1111/j.1096-3642.2012.00853.x
|View full text |Cite
|
Sign up to set email alerts
|

The early evolution of titanosauriform sauropod dinosaurs

Abstract: Titanosauriformes was a globally distributed, long‐lived clade of dinosaurs that contains both the largest and smallest known sauropods. These common and diverse megaherbivores evolved a suite of cranial and locomotory specializations perhaps related to their near‐ubiquity in Mesozoic ecosystems. In an effort to understand the phylogenetic relationships of their early (Late Jurassic–Early Cretaceous) members, this paper presents a lower‐level cladistic analysis of basal titanosauriforms in which 25 ingroup and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
483
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(518 citation statements)
references
References 88 publications
(329 reference statements)
32
483
3
Order By: Relevance
“…Originally established with a node-based definition (D Andesaurus delgadoi C Titanosauridae and all descendants of their most recent common ancestor; Salgado et al 1997), some subsequent works adopted a stem-based definition for the name and anchored the definition on other, more specific taxa (D all titanosauriforms more closely related to Saltasaurus loricatus than to Euhelopus zdanskyi; Sereno 1998; Wilson & Sereno 1998); then it was used again as a node-based name (D Andesaurus delgadoi C Saltasaurus loricatus and all descendants of their most recent common ancestor, Wilson & Upchurch 2003). The discovery of new titanosauriform taxa in recent years has also produced new hypotheses of titanosauriform phylogeny (Curry Rogers 2005;Calvo et al 2007a,b;Gonz alez Riga et al 2009;D'Emic 2012;Mannion et al 2013;Carballido & Sander 2014), which have sometimes resulted in taxonomic redundancy stemming from the shuffling of taxa used to anchor taxonomic definitions. For the purpose of this paper, we will follow the principle of priority whenever possible, adopting the first definition of a clade or lineage with an ancestry-based stem or node definition.…”
Section: Taxonomic Definitionsmentioning
confidence: 99%
“…Originally established with a node-based definition (D Andesaurus delgadoi C Titanosauridae and all descendants of their most recent common ancestor; Salgado et al 1997), some subsequent works adopted a stem-based definition for the name and anchored the definition on other, more specific taxa (D all titanosauriforms more closely related to Saltasaurus loricatus than to Euhelopus zdanskyi; Sereno 1998; Wilson & Sereno 1998); then it was used again as a node-based name (D Andesaurus delgadoi C Saltasaurus loricatus and all descendants of their most recent common ancestor, Wilson & Upchurch 2003). The discovery of new titanosauriform taxa in recent years has also produced new hypotheses of titanosauriform phylogeny (Curry Rogers 2005;Calvo et al 2007a,b;Gonz alez Riga et al 2009;D'Emic 2012;Mannion et al 2013;Carballido & Sander 2014), which have sometimes resulted in taxonomic redundancy stemming from the shuffling of taxa used to anchor taxonomic definitions. For the purpose of this paper, we will follow the principle of priority whenever possible, adopting the first definition of a clade or lineage with an ancestry-based stem or node definition.…”
Section: Taxonomic Definitionsmentioning
confidence: 99%
“…Several compressed cone-chisel teeth were found in the Upper Jurassic sedimentary sequence of the Lusitanian Basin (Alcobaça, Praia da AmoreiraPorto Novo, Sobral, Freixial, and Bombarral Formations). This tooth morphology was traditionally considered as synapomorphic of Titanosauriformes (e.g., Upchurch et al, 2004;D'Emic, 2012), but this morphology was also found in the possible basal macronarian Europasaurus (Carballido and Sander, 2014), which was also considered to be a member of Titanosauriformes by D'Emic (2012) and Mannion et al (2013). If we accept the phylogenetic position proposed for Europasaurus by Carballido and Sander (2014), this tooth morphology should be present in a more inclusive group than Titanosauriformes.…”
Section: Sauropod Palaeobiodiversity and Lithostratigraphic Distributmentioning
confidence: 99%
“…All this previous work and the detailed description of the material (Sanz et al, 1999;Company et al, 2009;Company, 2011;Díez Díaz et al, 2011, 2012, 2013, as well as its inclusion in numerous phylogenetic analyses, have made Lirainosaurus astibiae one of the world's best-known titanosaurian species, and a main reference for the study of the sauropod faunas of the Late Cretaceous of Europe.…”
Section: Introductionmentioning
confidence: 99%